Minority report: the intestinal mycobiota in systemic infections. (August 2020) - Rolling, Thierry; Hohl, Tobias M; Zhai, Bing
Highlights: The human mycobiota contains clinically relevant fungal species. Longitudinal sampling provides robust insights into the human mycobiota. Simultaneous analysis of intestinal fungi and bacteria is critical in clinical studies. The intestinal mycobiota is an important source of fungal bloodstream infections. The mycobiota may play a role in bacterial or viral systemic infections. Abstract : Compared to bacteria, fungi often exhibit a lower abundance and a higher temporal volatility in the intestinal microbiota. Analysis of fungi in the microbiota (mycobiota) faces technical limitations with tools that were originally developed for analyzing bacteria. Dysbiotic states of the intestinal mycobiota, often associated with disruption of the healthy bacterial microbiota, are characterized by overgrowth (domination) of specific fungal taxa and loss of diversity. Intestinal domination by Candida species has been shown to be a major source of Candida bloodstream infections. Fungal dysbiosis is also linked to the development and treatment response in non-fungal infections, for example Clostridioides difficile colitis and HIV. Further research is needed to define the contribution of intestinal mycobiota to human fungal and non-fungal infections.